Note from the Editor-in-Chief - Elivo, Ryan (Consilience, 2015)
Dear Readers, I am pleased to present the 14th Issue of Consilience: The Journal of Sustainable Development. Our Editorial and Managing Boards have worked tirelessly in the face of numerous structural changes to the group to bring you this issue, which is composed of 15 articles comprised of a cumulative 259 pages. 2015 will be a turning point for sustainable development, with the rollout of the Sustainable Development Goals and the convening of the 21st Conference of Parties at the end of the year. We hope that all of our readers will engage with our most current edition and follow the international discourse. Issue 14 features myriad subjects that transcend discipline and geography, all with major implications on the future of sustainability with regards to the following questions: (1) How can we reconcile the gaps that exist between normative language and tangible action, contradictory policies and unspoken priorities, and slow-moving policies and rapid technological advances? (2) How can we embrace the promises of rapidly advancing technology and knowledge while abandoning outmoded and wasteful practices? (3) Could some of these very frameworks and technologies that are lauded be harming the very marginalized populations they are supposed to be helping? With respect to the first question, Gregg Badichek discusses the conflict between renewable energy siting and endangered species conservation, before offering solutions under the existing framework. Gregor Beck, Cora Ditzel, Sofia Ganter, and Olga Perov examine the disparity between the growing literature on human rights and climate change and the extent to which the latter is truly articulated in the international climate negotiations. Megan Berry examines how “sustainability” is conceptualized linguistically and rhetorically within industry, utilizing the Canadian oil sands industry as a case study. Miranda Bernard, Alyssa Menz, and Laura Booth analyze the Magnet Effect in Central Kenya, which has implications for the future of ecosystem management. Joanna Caytas considers the inadequacies of decisionmaking and legal frameworks vis-à-vis technology assessment and systems analysis, which are not conducive to sustainable development. Nua Deedam and Anthony Onoja analyze the impact of Poverty Alleviation Programs on poverty reduction and the economic empowerment of Nigerian women. Liz Moyer presents an impact assessment model for an innovative scheme that is known as time banking, before linking it to the wider discourse on social capital and sustainable development. Cephas Mutami analyzes smallholder production as a potential pathway for fighting poverty in rural Zimbabwe. G. Owusu-Boateng and M.K. Gadogbe evaluate rainwater quality in Dzodze, Ghana and how it fluctuates from precipitation to storage. Simon Oginni and Joash Moitui consider meaningful policy measures that could be taken to boost public engagement in the electrical process using social media. Finally, Oyinbo Oyakhilomen, Adah Daniel, and Rekwot Zibah probe the technical efficiency of poultry egg production in Kaduna State, Nigeria with regard to sustainable food security. With regards to the third question, Rebecca Krisel investigates Gowanus, Brooklyn, a superfund site that is undergoing gentrification, with broad impacts on its residents. Joshua Mullenite chronicle the history of development in Guyana and the mistakes that have been made multiple times in the name of progress, with large human costs. Anthony Onoja and Anthonia Achike investigate land grabbing in West Africa by international investors, and consider the consequences for food security, property rights, and environmental sustainability. Finally, Jonathan Park appraises weak sustainability and the predominant neoliberal approach to valuing nature and addressing climate change, providing a wider critique of capitalism as it currently exists. The breadth of these subjects, from the role of metaphors in framing discourse to the omnipresence of macroeconomics and policy, reveals the complex obstacles that remain before humanity can truly realize sustainable development. 2015 will be a crucial turning point for sustainable development and international governance, with meaningful policy solutions in the pipeline. However, the significance of discourse and interdisciplinary engagement will only continue to grow as solutions to our world’s most pressing issues continue to emerge, and we at Consilience are excited to continue facilitating this discourse. We encourage you to continue engaging with the journal through your readership, submissions, and contributions to our Briefings column. As always, we welcome constructive feedback and hope that our work inspires you to engage with the issues. If you have any questions, comments, or concerns, please do not hesitate to contact us atcontact@consiliencejournal.org. We hope you enjoy Issue 14. Ryan Elivo Editor-in-Chief Consilience: The Journal of Sustainable Development June 12, 2015